The Influence of Illustrated Storybooks on the Reading Literacy Skills of Early Childhood Children - Ulfa; Ernita; Sistaliana; M.Rusdi Syawaludin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Education is not only centered on the transfer of knowledge but also plays a vital role in shaping character, values, and ethics, which serve as the foundation for national development. In today's digital era, young generations face new challenges due to the rapid advancement of information technology, such as instant culture, the spread of misinformation, and declining social empathy. Therefore, character education is crucial in developing a resilient, moral, and responsible generation. This study aims to examine the importance of character education in the digital age and the role of educational media, such as picture storybooks, in strengthening early childhood literacy. The method used is library research with a descriptive-qualitative approach. The results show that picture storybooks significantly contribute to improving early childhood literacy skills through visualization, vocabulary enhancement, narrative structure, as well as the development of empathy and emotional intelligence. Picture books also support holistic learning and can be integrated into various aspects of early childhood education curricula. In conclusion, character education and early childhood literacy must be optimized simultaneously, involving the collaboration of teachers, parents, and communities, while utilizing relevant and engaging learning media such as picture storybooks.